1986
DOI: 10.1148/radiology.159.2.2938213
|View full text |Cite
|
Sign up to set email alerts
|

Posterior atlantooccipital subluxation in Down syndrome.

Abstract: Three Down syndrome patients with posterior atlantooccipital (AO) subluxation are described. All are asymptomatic. The subluxation becomes manifest during active extension of the neck and reduces in flexion. Methods of assessing posterior AO subluxation are discussed. The abnormality is attributed to ligamentous laxity in patients with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Occipitoatlantoaxial instability has been reported infre quently [33][34][35]. The natural history and contribution of this dislocation in Down's syndrome is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occipitoatlantoaxial instability has been reported infre quently [33][34][35]. The natural history and contribution of this dislocation in Down's syndrome is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We reported our earlier series in 1980 with Down's syndrome and occipitoatlan toaxial instability responding to traction, dorsal occipito cervical fusion and halo cast immobilization [ 19], In 1986. El'Khoury et al [33] described 3 patients with posterior occipital translation, 2 of whom showed no atlantoaxial instability, and 1 had a spontaneously reducible rotary lux ation of Cl. Rosenbaum et al [36] described two cases of asymptomatic atlantoaxial instability in Down's syn drome.…”
Section: Discussionmentioning
confidence: 99%
“…Atlanto-occipital subluxation was first reported in association with Down syndrome in 1981 18 and, in contrast with that seen in trauma, is almost always posterior. Other groups of patients have been described by El-Khoury, 19 Brooke, 5 Tredwell, 7 Stein 4 and most recently by Parfenchuck. 6 In 1991, Stein presented five new patients and reviewed nine others previously presented in the literature.…”
Section: Discussionmentioning
confidence: 93%
“…[1,20,27,31,32] Atlantooccipital instability and rotary luxation of the atlas are well described in patients with Down's syndrome and should not be overlooked. [11,27,33,37,39,44] Parfenchuck, et al, [30] have suggested that the incidence of posterior atlantooccipital hypermobility in Down's syndrome is 8.5%. Bony anomalies such as os odontoideum and hypoplasia of various craniovertebral elements, including the atlantal ring and condyles, likely increase the risk for instability at the CVJ.…”
Section: Discussionmentioning
confidence: 99%
“…[11,17,24,30,42,43] Clinical correlations were not made in the first description of antlantooccipital luxation by Spitzer, et al [40] Neurological abnormalities have been found in up to 66% of patients with antlantooccipital pitoatlantal instability. [30] In a prospective review of 64 patients with antlantooccipital instability, 61% of the patients were shown to have a posterior occipital subluxation greater than 4 mm and 21% to have a predental space of greater than 5 mm.…”
Section: Discussionmentioning
confidence: 99%